Radar micro-Doppler signatures : processing and applications - Chen, Victor C.; Tahmoush, David; Miceli, William J. (IET radar, sonar, navigation and avionics series ;, 2014)
This book concentrates on the processing and application of radar micro-Doppler signatures in real world situations, providing readers with a good working knowledge on a variety of applications of radar micro-Doppler signatures. Topics covered include; bistatic/multistatic micro-Doppler signatures, decomposition of micro-Doppler signatures, through-wall radar micro-Doppler signatures and ultrasound micro-Doppler signature studies. Real world applications discussed include: detection, tracking and discrimination of targets with movements; analysis and identifying human movement; analysis and identifying helicopters; detection and tracking small boats in sea; analysis of wind turbines. --